To solve this expression, let's simplify it step by step:
First, let's simplify the division of -3 by 3/4:
(-3) ÷ (3/4) = -3 × (4/3)
Next, let's multiply the result by 2/7:
-3 × (4/3) × (2/7)
Now, let's multiply the result by -5/16:
-3 × (4/3) × (2/7) × (-5/16)
Finally, let's divide the result by 5/7:
-3 × (4/3) × (2/7) × (-5/16) ÷ (5/7)
Now, let's simplify:
-3 × (4/3) = -4
-4 × (2/7) = -8/7
-8/7 × (-5/16) = 40/112 = 5/14
5/14 ÷ (5/7) = 5/14 × (7/5) = 35/70 = 1/2
Therefore, (-3)÷(3/4)×(2/7)×(−5/16)÷(5/7) = 1/2.
(−3)÷(3/4)×(2/7)×(−5/16)÷(5/7)
1 answer